Treatment Efficacy, Adherence, and Quality of Life Among Women Younger Than 35 Years in the International Breast Cancer Study Group TEXT and SOFT Adjuvant Endocrine Therapy Trials - (:unkn) unknown (AMER SOC CLINICAL ONCOLOGY, 2017)
Purpose To describe benefits and toxicities of adjuvant endocrine therapies in women younger than 35 years with breast cancer (n = 582) enrolled in the Suppression of Ovarian Function Trial (SOFT) and Tamoxifen and Exemestane Trial (TEXT). Methods In SOFT, women still premenopausal after surgery with or without chemotherapy were randomly assigned to tamoxifen alone, tamoxifen plus ovarian function suppression (OFS), or exemestane plus OFS. In TEXT, all received OFS with or without concomitant chemotherapy and were randomly assigned to exemestane plus OFS or tamoxifen plus OFS. We summarize treatment efficacy, quality of life, and adherence of the cohort of women younger than 35 years in SOFT and TEXT, alongside data from the cohort of older premenopausal women. Results For 240 human epidermal growth factor receptor 2-negative patients younger than 35 years enrolled in SOFT after receiving chemotherapy, the 5-year breast cancer-free interval (BCFI) was 67.1% (95% CI, 54.6% to 76.9%) with tamoxifen alone, 75.9% with tamoxifen plus OFS (95% CI, 64.0% to 84.4%), and 83.2% with exemestane plus OFS (95% CI, 72.7% to 90.0%). For 145 human epidermal growth factor receptor 2-negative patients younger than 35 years in TEXT, 5-year BCFI was 79.2% (95% CI, 66.2% to 87.7%) with tamoxifen plus OFS and 81.6% (95% CI, 69.8% to 89.2%) with exemestane plus OFS. The most prominent quality of life symptom for patients younger than 35 years receiving OFS was vasomotor symptoms, with the greatest worsening from baseline at 6 months (on the order of 30 to 40 points), but loss of sexual interest and difficulties in becoming aroused were also clinically meaningful (>= 8-point change). The level of symptom burden was similar in older premenopausal women. A total of 19.8% of women younger than 35 years stopped all protocol-assigned endocrine therapy early. Conclusion In women younger than 35 years with hormone receptor-positive breast cancer, adjuvant OFS combined with tamoxifen or exemestane produces large improvements in BCFI compared with tamoxifen alone. Menopausal symptoms are significant but are not worse than those seen in older premenopausal women.
Keywords: PATIENT-REPORTED OUTCOMES; PREMENOPAUSAL WOMEN; OVARIAN SUPPRESSION; HORMONAL-THERAPY; NONADHERENCE; TAMOXIFEN; EXEMESTANE